Medium-term variability of the UK's combined tidal energy resource for a net-zero carbon grid. (1st January 2022) - Todeschini, G.; Coles, D.; Lewis, M.; Popov, I.; Angeloudis, A.; Fairley, I.; Johnson, F.; Williams, A.J.; Robins, P.; Masters, I.
Abstract: The small area of the United Kingdom relative to weather systems makes renewable energy sources variable on short time scales. Short term variability is therefore a growing concern with increasing amounts of renewable energy integration. In this work, we address how tidal energy can contribute to reducing medium-term variability in the future UK energy mix. Two tidal integration scenarios are defined for 2050: for each scenario, a 5-min interval generation profile is calculated using an oceanographic model of UK tides, and the medium-term variability is assessed. Here we show that tidal power shows a lower level of variability compared to other resources. During spring tides, a national network of tidal power stations can produce continuous, although variable, electricity. It is then shown that tidal energy and storage can provide year-round continuous and constant power output, i.e. baseload generation. Therefore, we conclude that tidal energy can provide positive contributions and complement other renewable energy sources. Graphical abstract: Image 1 Highlights: Tidal energy can become a valuable complementary renewable energy source. Tidal power shows a lower level of variability compared to other resources. During spring tides, a network of tidal plants can produce continuous electricity. Tidal energy combined with energy storage can provide baseload generation.